New Technique: A Novel Femoral Derotation Osteotomy for Malrotation following Intramedullary Nailing - S. Jagernauth; A. J. Tindall; S. Kohli; P. Allen (Case Reports in Orthopedics)
A 19-year-old female patient sustained a closed spiral midshaft femoral fracture and subsequently underwent femoral intramedullary nail insertion. At followup she complained of difficulty in walking and was found to have a unilateral in-toeing gait. CT imaging revealed 30 degrees of internal rotation at the fracture site, which had healed. A circumferential osteotomy was performed distal to the united fracture site using a Gigli saw with the intramedullary femoral nail in situ. The static distal interlocking screws were removed and the malrotation was corrected. Two further static distal interlocking screws were inserted to secure the intramedullary nail in position. The osteotomy went on to union and her symptoms of pain, walking difficulty, and in-toeing resolved. Our paper is the first to describe a technique for derotation osteotomy following intramedullary malreduction that leaves the intramedullary nail in situ.